2020
DOI: 10.1155/2020/3059435
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Modern Contraceptive Methods Discontinuation among Women within Reproductive Age in Dire Dawa City, Eastern Ethiopia

Abstract: Background. Modern family planning methods are widely believed to influence fertility reduction worldwide. Family planning had a clear effect on the health of women, children, and families worldwide especially those in developing countries. It has been shown that there are many instances in which women might discontinue contraception methods that put women’s health at risk. Objectives. To assess and identify Determinants of Modern Contraceptive Methods Discontinuation among Women in Reproductive age interval i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 7 publications
1
8
0
Order By: Relevance
“…ARM results demonstrated that women in their early reproductive years (25–34 years) more often discontinued the use of contraceptives. This result was supported by studies conducted in Bangladeshi [ 26 ], six countries DHS (Bangladesh, Philippines, Kazakhstan, Dominican Republic, Kenya, and Zimbabwe) which showed that women who had discontinued contraception were somewhat concentrated in the 25–34 ages [ 18 ], and a study in Ethiopia which stated that woman whose age is between 25 and 34 had a higher risk of discontinuing modern contraceptive methods [ 70 ]. This may be due to the reason thinking of reaching the menopausal period in the older mothers [ 9 ] which may urge them to have a child as early as possible.…”
Section: Discussionmentioning
confidence: 83%
“…ARM results demonstrated that women in their early reproductive years (25–34 years) more often discontinued the use of contraceptives. This result was supported by studies conducted in Bangladeshi [ 26 ], six countries DHS (Bangladesh, Philippines, Kazakhstan, Dominican Republic, Kenya, and Zimbabwe) which showed that women who had discontinued contraception were somewhat concentrated in the 25–34 ages [ 18 ], and a study in Ethiopia which stated that woman whose age is between 25 and 34 had a higher risk of discontinuing modern contraceptive methods [ 70 ]. This may be due to the reason thinking of reaching the menopausal period in the older mothers [ 9 ] which may urge them to have a child as early as possible.…”
Section: Discussionmentioning
confidence: 83%
“…Dire Dawa has a health service coverage of 95%, with two public hospitals (Dilchora and Sabiyan) equipped with neonatal intensive care units (NICUs) ( 13 ). Also, Harari is one of the 11 regions, located 526 km from Addis Ababa ( 14 , 15 ). Harari has two public hospitals (Hiwot Fana and Jugol) equipped with NICUs.…”
Section: Methodsmentioning
confidence: 99%
“…This finding is in agreement with previously conducted research studies in Arba Minch, Ethiopia; evidence from the 2016 Ethiopian DHS and Dire Dawa city, Ethiopia revealed that women supported by their husbands for the decision of contraceptive use are less likely to remove LARC methods. 4 , 11 , 12 , 20 A possible explanation could be disapproval of the husbands of contraceptive method utilization. In Ethiopia, men are the primary decision-makers for most family issues, including reproductive health issues like either continuing to use or removing contraceptive methods.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, study conducted in Dire Dawa revealed that 21.8% of contraceptive users discontinued the method within a year related to contributing factors such as age, lower parity, and not being decision-maker to use the methods. 12 …”
Section: Introductionmentioning
confidence: 99%